Mineral and water content of A. gigas scales determine local micromechanical properties and energy dissipation mechanisms - Troncoso, O.P.; Gigos, F.; Torres, F.G. (Springer Netherlands, 2017)
Arapaima gigas scales are natural laminated composite materials made of individual layers with different degrees of mineralization, accompanied of varying mechanical properties. This natural design provides scales with hardness and flexibility, and can serve as a source of inspiration for the development of new layered composites with a hard surface and flexible base. In this paper, we have carried out cyclic micro-indentation tests on both; the internal and the highly mineralized external surface of air dried and wet scales, in order to assess the variation of their local micromechanical properties with regard to the mineral and water content. The load–penetration (P–h) curves showed that creep takes place throughout the application of a constant force during the micro-indentation tests, confirming the time dependent response of A. gigas scales. A model that accounted for the elastic, plastic and viscous responses of the samples was used to fit the experimental results. The penetration depth during loading and creep, as well as the energy dissipated are dependent on the water content. The used model suggests that the viscous response of the internal layer increases with the water content.
Keywords: Arapaima gigas; Fish scale; Indentation; Energy dissipation; https://purl.org/pe-repo/ocde/ford#1.06.00